THE CYTOTOXICITY OF ORTHODONTIC POLYMERIC BIOMATERIALS - SODOR ALINA; ZEGAN GEORGETA; GOLOVCENCU LOREDANA; ANISTOROAEI DANIELA (Romanian Society of Oral Rehabilitation, 2018)
The objective of our study was to evaluate in vitro the cytotoxicity of different intraoral elastic chains and elastomeric ligatures that are used as components of orthodontic fixed appliances. The study evaluated the reaction of tree groups: the negative control group (human fibroblasts cultures), the positive control group (dental copper amalgam) and the study group represented by intraoral orthodontic elastics: elastic chain (Orthoclassic) and elastomeric ligatures of different colors and latex consistency from different manufacturers (Orthoclassic and GAC). After 3 and respective 6 days we analyzed the samples by direct method and microscopic analysis (Nikon Eclipse TE300). We analyzed the shape of the fibroblasts around the material, their number and the morphologic alterations of the cells. The analysis of the fibroblasts situated at distance from the material and the percent of the vital cells was obtained by comparing the maxim cells density of the negative control group with the density of the study groups. The dental copper amalgam determined the apoptosis of all the cells of the group and showed a high cytotoxicity. The elastic chain Orhoclassic determined important morphologic changes on human fibroblasts cultures and showed a reduced biocompatibility. The elastomeric ligatures Orthoclassic with low elasticity showed a relative biocompatibility. The elastomeric ligatures Orthoclassic with high elasticity showed a good biocompatibility. The elastomeric ligatures GAC showed a relative compatibility at 3 days but a high cytotoxicity at 6 days.